Identification and control of nosocomial adenovirus keratoconjunctivitis in an ophthalmic department. Issue 1 (12th August 2008) - Dart, J K G; El-Amir, A N; Maddison, T; Desai, P; Verma, S; Hughes, A; MacMahon, E
Abstract : Aims: To identify the extent of nosocomial adenovirus keratoconjunctivitis (AKC) and assess the effect of a new infection-control policy. Methods: Nosocomial AKC was defined as AKC in patients attending the hospital within 3 weeks of a previous visit for an unrelated non-infective condition. An audit of culture-proven nosocomial AKC was carried out from October 1998 to September 1999 to establish its extent in our outpatient department. A new infection-control policy for AKC was introduced in June 2001 that differed from the previous policy by segregating suspected AKC cases in a separate waiting area and examination room, and by expediting their examination, to reduce their exposure to both staff and patients in the common waiting areas. In October 2002, AKC was made an index infection and subjected to continual quarterly audit; the figures for this until December 2005 are reported. Results: In the 1998–9 audit, before the introduction of the new infection-control measures, 48.4% (75/155) AKC infections were nosocomial. In the 12 months following the introduction of the quarterly audit in October 2002, 22.7% (5/22) were nosocomial, but thereafter the numbers of nosocomial cases dropped to 3.4% (8/235). Conclusion: Introduction of audit of nosocomial AKC infection identified that there was chronic cross-infection in the Moorfields Eye Hospital Accident and Emergency Department. This was controlled by the introduction of patient segregation, as an additional infection-control measure, which has almost eliminated nosocomial AKC transmission in the hospital.